IMPACT OF MOTIVATION THEORIES ON EMPLOYEE’S PERFORMANCE W.R.T SELECTED MANUFACTURING INDUSTRY - Maheswara Vishnu Sai, Maddukuri (The journal of contemporary issues in business and government, 2022)
Management has a crucial part to play in helping people find work that is more enjoyable and rewarding for them, as well as in ensuring that the motivation of employees is aligned with the goals of the business. This is a challenging endeavour because of the many different types of people that work in modern companies. The things that individuals value and the things that are gratifying to them are influenced by a variety of variables, one of which is the various cultures to which they belong. This research takes the point of view of a manager and seeks to get an understanding of what motivates individuals, what impacts them, and why they continue to engage in certain behaviours. The motivational levels of the organization’s staff members will also be investigated as part of this research. It is very necessary to have an effective programme technique for motivating employees in order to accomplish the organization’s goals. With effective employee motivationprograms not only this organization,it would help every organization to accomplish its potential maxima and also establish a good organizational culture with the achievement of organizational objectives. In order for a business to realise its objectives, it is critical to provide its workforce with the inspiration and support necessary to achieve success in their professional endeavours. There are a variety of extrinsic and intrinsic elements that contribute to an employee’s level of motivation. Today, it would seem that this selected manufacturing firm is facing challenges w.r.t employeemotivation for a number of different reasons, which acted as an impediment to customer satisfaction and timely delivery of goods and services. The purpose of this research is to determine the elements that contribute to motivation and the relationship between motivation and performance on the job. A positive working environment, the opportunity to gain quality experience, alignment of skills and job done by employees, and benefit packages were found to have a significant effect on both employees’ levels of motivation and their performance on the job. Based on a significant period of observation after implementing the motivational techniques, it was noticeably clear that the motivated employees add to organizational efficiency and played a pivotal role in successfully curbing the problem of late delivery and increasing customer satisfaction. These findings were the primary conclusions drawn from this research.